Accurate numerical simulation of turbulent natural convection in an enclosed tall cavity. (2017) - Wang, Changshan; Gao, Ge; Zhao, Lihua; Schuetz, Winfried; Xu, Yugong
Abstract: Building simulation tools play an important role in the field of building physics. The performance of these tools relies on the understanding of related physic phenomenon and needs to be ensured by the validation. Nowadays, numbers of building simulation tools have been developed. However, most of these tools lack internationally accepted experimental data for validation. As for the investigation of combined heat, air and moisture (HAM) transfer process, it is limited by the fact that it is difficult to measure air and moisture fluxes and moisture transport potentials, even under laboratory conditions. In this paper, the author established a numerical laboratory to overcome the difficulty of measuring air and mass flux within enclosed cavity. The performance of new developed simulation approach in predicting convective flow characteristics of dry air has been validated. Then convective flow characteristics of moist air within enclosed cavity have been investigated.